A case study of personalized therapy for osteosarcoma. Issue 8 (22nd March 2013) - Davis, Lara E.; Hofmann, Nicolle E.; Li, Guangheng; Huang, Elaine T.; Loriaux, Marc M.; Bracha, Shay; Helfand, Stuart C.; Mata, John E.; Marley, Kevin; Mansoor, Atiya; Tyner, Jeffrey W.; Abraham, Jinu; et al.
Abstract Background Effective targeted therapies are needed in sarcomas, but the biological heterogeneity of these tumors has presented a challenge to clinical integration of small molecule inhibitors in sarcoma treatment. Here we outline a process to personalize therapy for sarcomas through a case study of a canine with spontaneous osteosarcoma. Procedure Rapid establishment of a primary tumor cell culture is described, followed by efficient functional characterization of the tumor that identified the Src inhibitor dasatinib as the most effective targeted therapy for this individual dog. Results Adjuvant dasatinib was administered for a total of 26 weeks following treatment with chemotherapy. Pharmacokinetic studies confirm that a therapeutic serum concentration was achieved at a tolerable dose of 0.75 mg/kg/day. The canine patient remains without evidence of recurrent disease 24 months following initial diagnosis. Conclusions The approach described through this illustrative case study is broadly applicable and might be used for other solid tumors in canines as well as in humans. Pediatr Blood Cancer 2013;60:1313–1319. © 2013 Wiley Periodicals, Inc.